Diagnosing business incubation for social purpose: a viable system model approach - Adham, Khairul Akmaliah; Muhamad, Nur Sa’adah; Said, Mohd Fuaad; Abdul Sarhadat, Shahrizin; Ismail, Habib Asaril; Mohd Nasir, Mohd Fareez Assrul (Springer, 2019)
Business incubation is one of the means that promotes the overall business and economic growth of a particular location. However, to date, the role of business incubation as a social innovation, which has the aim to achieve concurrent development of firms, the economy and the society, is not yet understood. Using the systemic approach, specifically the viable system model (VSM) as the framework, the objective of this study is to diagnose the operation of an incubation programme that focuses on supporting business development for social purpose. This study utilized the qualitative methodology and selected an incubator, known as Kompleks Industri Makanan MARA (KIMAR), as the system-in-focus. KIMAR is a halal food industry complex established and operated by Majlis Amanah Rakyat (MARA); the latter a Malaysian government agency that aims to promote the socio-economic empowerment of the indigenous people of Malaysia including the Malays. Data for the diagnosis was collected through interviews with the executives responsible for the incubator operation, as well as the managers or entrepreneurs of the businesses located within it. Our analysis found cohesions among the functions of the incubator and their functionality to manage certain varieties in the environment, although more requisite varieties are needed to manage the high complexity of global halal business development. In managing these varieties, the incubation process receives financial sponsorship and other support from its social-based parent organization. The use of systems perspective highlights operational values of responsibility, long-term perspective as well as effective management of resources that drive the impact of a social incubator, thus enriches the concept of social innovation that typically focuses on the social impact of the outcome.